Persistent cognitive and morphological alterations induced by repeated exposure of adolescent rats to the abused inhalant toluene - Braunscheidel, K.M. (Neurobiol Learn Mem, 2017)
While the psychoactive inhalant toluene causes behavioral effects similar to those produced by other drugs of abuse, the persistent behavioral and anatomical abnormalities induced by toluene exposure are not well known. To mimic human “binge-like” inhalant intoxication, adolescent, male Sprague-Dawley rats were exposed to toluene vapor (5700 ppm) twice daily for five consecutive days. These rats remained in their home cages until adulthood (P60), when they were trained in operant boxes to respond to a palatable food reward and then challenged with several different cognitive tasks. Rats that experienced chronic exposure to toluene plus abstinence (“CTA”) showed enhanced performance in a strategy set-shifting task using a between-session, but not a within-session test design. CTA also blunted operant and classical conditioning without affecting responding during a progressive ratio task. While CTA rats displayed normal latent inhibition, previous exposure to a non-reinforced cue enhanced extinction of classically conditioned approach behavior of these animals compared to air controls. To determine whether CTA alters the structural plasticity of brain areas involved in set-shifting and appetitive behaviors, we quantified basal dendritic spine morphology in DiI-labeled pyramidal neurons in layer 5 of the medial prefrontal cortex (mPFC) and medium spiny neurons in the nucleus accumbens (NAc). There were no changes in dendritic spine density or subtype in the mPFC of CTA rats while NAc spine density was significantly increased due to an enhanced prevalence of long-thin spines. Together, these findings suggest that the persistent effects of CTA on cognition are related to learning and memory consolidation/recall, but not mPFC-dependent behavioral flexibility.